Efektivitas Akupuntur terhadap Pemulihan Fungsi Kognitif pada Pasien Post Stroke: The Effectiveness of Acupuncture on Cognitive Function Recovery in Post-Stroke Patients - Agus Purnama; Susaldi (Journal of Nursing Education and Practice, 2023)
Introduction: Stroke is a leading cause of long-term disability and mortality worldwide. One of the most common complications following a stroke is cognitive impairment, which significantly affects the patient’s quality of life. Acupuncture, as a complementary therapy, has been widely used to support neurological recovery, including improvements in cognitive function. Objectives: This study aimed to evaluate the effectiveness of acupuncture in improving cognitive function among post-stroke patients. Method: A randomized controlled trial was conducted involving nine post-stroke patients undergoing acupuncture therapy. Cognitive function was assessed using the Mini-Mental State Examination (MMSE) before and after the intervention. Data were analyzed using a paired t-test. Result: The average cognitive function score increased from 18.6 (SD = 4.16) before the intervention to 28.2 (SD = 3.93) after the intervention, with a statistically significant difference (p = 0.001). The most substantial improvement was observed in the eighth session, with a mean increase of 8 points. Conclusion: Acupuncture is effective in enhancing cognitive function among post-stroke patients. It can serve as a supportive complementary nursing intervention in stroke rehabilitation programs.